Psychosocial factors in children presenting with poisoning in a tertiary care centre - Harsha, K. Sri; Channawar, Kanchan S.; Divya, Buthu (International Journal of Contemporary Pediatrics, 2025)
Background: Poisonings in children pose a significant challenge for paediatricians in India due to the diversity of substances and their clinical manifestations. This study investigates the psychosocial factors contributing to acute poisoning among children, aiming to identify key risk factors. Methods: A prospective, observational study was conducted on 50 children under 18 years admitted for poisoning at Kamineni Academy of Medical Science and Research Centre, Hyderabad, over 24 months (September 2022–September 2024). Data on age, sex, socio-demographic details, poison type, route of exposure, time to hospital arrival, storage practices, and psychosocial factors were analyzed. Results: Findings reveal that most poisoning cases occurred in children under five years, with 94% being accidental. Hydrocarbons accounted for 36% of cases, with three-fourths of incidents involving children aged 1–6 years. Rural areas contributed to 56% of cases, and poisoning incidents peaked during the summer (54%). A majority (58%) of cases were from lower socioeconomic backgrounds. All cases involved ingestion, and survival rates were 100%. Psychosocial analysis indicated significant risks associated with family dynamics: lack of emotional support, parental psychological illness, and substance abuse were observed in cases of suicidal poisoning. Conclusions: Childhood poisoning is a critical medical emergency with substantial morbidity. Beyond accidental incidents, it highlights underlying behavioral and family maladaptations, emphasizing the need for early psychosocial interventions to mitigate long-term consequences.